Biological treatment of acid mine drainage under sulphate-reducing conditions with solid waste materials as substrate - Chang, IS; Shin, PK; Kim, BH (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
Organic waste materials were tested as the electron donors for sulphate reducers in treating acid mind drainage. They are oak chips (OC), spent oak From shiitake farms (SOS), spent mushroom compost (SMC), sludge from a wastepaper recycling plant (SWP) and organic-rich soil (ORS). The materials were placed in column reactors, which were inoculated by anaerobic digester fluid. The number of sulphate-reducers increased to 10(8)-10(9) cells/ml in 2 weeks in the reactors. The reactors were continuously fed with simulated mine drainage for 35 weeks to determine sulphate reduction and metal removal. SOS, SMC and SWP served better as electron donors than OC and ORS. Metal removal efficiency of the reactor with OC was lower than those with SOS, SMC and SWP at the beginning, but became comparable at a later stage. The solvent extractable of OC inhibited the growth of sulphate-reducers. Cellulose polysaccharides were the main components of the waste materials consumed in the reactors. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: BACTERIAL SULFATE-REDUCTION; RESIN ACIDS; WATER; LIMESTONE; LIGNIN; WHEAT